The Relationship between Academic Stress and the Tendency of Eating Disorders in Students at Makassar State University - Renaldi, Renaldi; Murdiana, Sitti (Polteknik Ilmu Pemasyarakatan, 2025)
The prevalence of tendencies towards eating disorders is increasing, with academic stress being identified as one of the contributing factors. This study aims to investigate the relationship between academic stress and the tendency toward eating disorders among students at Universitas Negeri Makassar. The study involved 198 students from three faculties at Universitas Negeri Makassar: The Faculty of Education (FIP), the Faculty of Social and Legal Sciences (FIS-H), and the Faculty of Psychology (FPsi). The sampling technique used was Accidental Sampling. The research instruments included the Educational Stress Scale for Adolescents (ESSA) and the Eating Attitude Test-26 (EAT-26). The results of the Spearman rho correlation analysis showed a significant relationship between academic stress and the tendency toward eating disorders among students (p = 0.000 < 0.05). The correlation coefficient between academic stress and the tendency toward eating disorders was +0.397, indicating a moderate relationship. This research contributes to understanding the factors affecting mental health and eating disorders among students and serves as a foundation for more effective interventions in addressing academic stress in the university environment.